The anomalous origin and branches of the obturator artery with its clinical implications - A R Jusoh; Nurzarina Abd Rahman,; Azian Abd Latiff,; Faizah Othman,; S Das,; Norzana Abd Ghafar,; Farihah Haji Suhaimi,; Farida Hussan,; Israa Maatoq Sulaiman (Editura Academiei Romane, 2024)
The obturator artery (OA) originates from the internal iliac artery. Variation in the origin of the OA may be asymptomatic in individuals and occasionally be detected during routine cadaveric dissections or autopsies. In the present study, we observed the origin and the branching pattern of the OA on 34 lower limbs (17 right sides and 17 left sides) irrespective of sex. The bifurcation of the common iliac artery into internal and external iliac from the sacral ala varied between 4.3-5.3 cm. The distance of the origin of the anterior division of internal iliac artery from the bifurcation of common iliac artery varied between 1-6 cm. The distance of the origin of the posterior division of the internal iliac artery from the point of bifurcation of the common iliac artery varied between 0-6 cm. Out of 34 lower limbs studied, two specimens (5.8%) showed anomalous origin of the OA originating from the posterior division of the internal iliac artery. Of these two, one limb belonged to the right side while the other was from the left side. The anomalous OA gave off an inferior vesical branch to the prostate in both the specimens. No other associated anomalies regarding the origin or branching pattern of the OA were observed. Prior knowledge of the anatomical variations may be beneficial for vascular surgeons ligating the internal iliac artery or its branches and the radiologists interpreting angiograms of the pelvic region.